Formation of artificial chromosomes in Caenorhabditis elegans and analyses of their segregation in mitosis, DNA sequence composition and holocentromere organization. Issue 16 (20th August 2021) - Lin, Zhongyang; Xie, Yichun; Nong, Wenyan; Ren, Xiaoliang; Li, Runsheng; Zhao, Zhongying; Hui, Jerome Ho Lam; Yuen, Karen Wing Yee
Abstract: To investigate how exogenous DNA concatemerizes to form episomal artificial chromosomes (ACs), acquire equal segregation ability and maintain stable holocentromeres, we injected DNA sequences with different features, including sequences that are repetitive or complex, and sequences with different AT-contents, into the gonad of Caenorhabditis elegans to form ACs in embryos, and monitored AC mitotic segregation. We demonstrated that AT-poor sequences (26% AT-content) delayed the acquisition of segregation competency of newly formed ACs. We also co-injected fragmented Saccharomyces cerevisiae genomic DNA, differentially expressed fluorescent markers and ubiquitously expressed selectable marker to construct a less repetitive, more complex AC. We sequenced the whole genome of a strain which propagates this AC through multiple generations, and de novo assembled the AC sequences. We discovered CENP-A HCP-3 domains/peaks are distributed along the AC, as in endogenous chromosomes, suggesting a holocentric architecture. We found that CENP-A HCP-3 binds to the unexpressed marker genes and many fragmented yeast sequences, but is excluded in the yeast extremely high-AT-content centromeric and mitochondrial DNA (> 83% AT-content) on the AC. We identified A-rich motifs in CENP-A HCP-3 domains/peaks on the AC and on endogenous chromosomes, which have some similarity with each other and similarity to some non-germline transcription factor binding sites.